2015
DOI: 10.1073/pnas.1507393112
|View full text |Cite
|
Sign up to set email alerts
|

AMCase is a crucial regulator of type 2 immune responses to inhaled house dust mites

Abstract: Chitinases are enzymes that cleave chitin, a component of the exoskeleton of many organisms including the house dust mite (HDM). Here we show that knockin mice expressing an enzymatically inactive acidic mammalian chitinase (AMCase), the dominant true chitinase in mouse lung, showed enhanced type 2 immune responses to inhaled HDM. We found that uncleaved chitin promoted the release of IL-33, whereas cleaved chitin could be phagocytosed and could induce the activation of caspase-1 and subsequent activation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
54
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 46 publications
3
54
2
Order By: Relevance
“…Still, additional reports have proposed that AMCase has a protective role. One showed that the type 2 inflammatory response following chitin challenge was ameliorated in mice overexpressing AMCase 8 , and another observed increased allergic lung disease in mice specifically lacking AMCase enzymatic activity 11 . The contrasting functional implications of AMCase highlighted in these studies have yet to be fully reconciled.…”
mentioning
confidence: 99%
“…Still, additional reports have proposed that AMCase has a protective role. One showed that the type 2 inflammatory response following chitin challenge was ameliorated in mice overexpressing AMCase 8 , and another observed increased allergic lung disease in mice specifically lacking AMCase enzymatic activity 11 . The contrasting functional implications of AMCase highlighted in these studies have yet to be fully reconciled.…”
mentioning
confidence: 99%
“…Consistent with the concept that chitin must be enzymatically broken down to avoid aberrant type 2 responses, mice deficient in the enzymatically active AMCase (AMCase-ED) have an exacerbated allergic airway inflammation in response to house dust mite (HDM) extract [11•]. Bone-marrow chimera studies showed that AMCase in structural cells, more so than hematopoeitically expressed (macrophage) AMCase, is central in mediating enhanced IL-33 and eosionophilia following allergen exposure [11•].…”
Section: Introductionmentioning
confidence: 99%
“…Bone-marrow chimera studies showed that AMCase in structural cells, more so than hematopoeitically expressed (macrophage) AMCase, is central in mediating enhanced IL-33 and eosionophilia following allergen exposure [11•]. Specifically, administration of chitin in the airways of mice leads to eosinophilia and mucus production.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations